2011
DOI: 10.1017/s0022109011000275
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Derivatives on Firm Risk and Value

Abstract: Using a large sample of nonfinancial firms from 47 countries, we examine the effect of derivative use on firm risk and value. We control for endogeneity by matching users and nonusers on the basis of their propensity to use derivatives. We also use a new technique to estimate the effect of omitted variable bias on our inferences. We find strong evidence that the use of financial derivatives reduces both total risk and systematic risk. The effect of derivative use on firm value is positive but more sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
177
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(239 citation statements)
references
References 56 publications
12
177
3
8
Order By: Relevance
“…The multiple regression reveals that of the three factors assumed to influence value of the firm using the Tobin's Q, only the profitability of the business was able to statistically affect the firm value using the Tobin's Q. Different investigators concluded that profitability has significant influence on firm value (Bartram et al 2011;Naito and Laux 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The multiple regression reveals that of the three factors assumed to influence value of the firm using the Tobin's Q, only the profitability of the business was able to statistically affect the firm value using the Tobin's Q. Different investigators concluded that profitability has significant influence on firm value (Bartram et al 2011;Naito and Laux 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Warren Buffett has described derivatives as “financial weapons of mass destruction” (Buffett, 2003) and many people have pointed to credit default swaps as having an important contributing role to the financial crisis of 2007–2009 (Financial Crisis Inquiry Commission, 2011). While it is true that options and futures potentially do have some economic value when used to hedge risk (Bartram, Brown, & Conrad, 2011; Moschini & Lapan, 1995), they do not have this value when used for speculative purposes, which they often are. Furthermore, the latest research would suggest that options and futures contribute to destabilization of market prices (Somanathan & Anantha Nageswaran, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…They obtained a hedging premium (on average, between 9% and 20%) for firms with strong internal corporate governance (such as those with institutional investors) and those which reside in countries with strong external governance (such as those with English-based laws that especially protects investor's rights). Bartram, Brown, and Conrad (2011) also studied a broad sample of firms from 47 countries between 1998 and 2003. They obtained that hedging firms have 10-25% lower cash flow volatility, 3-10% lower standard deviation of returns, 6-22% lower betas and 1-7% higher value than non-hedging firms.…”
Section: Related Literaturementioning
confidence: 99%
“…Chung and Pruitt (1994) propose the market to book ratio as an alternative way of estimating Tobin's Q. The primary advantage of this method is its simplicity, which allows us to create values for all firms (Bartram, Brown, and Conrad 2011). As pointed out by DaDalt, Donaldson, and Garner (2002), this is especially important because most studies are based on samples where the availability of data is a critical issue.…”
Section: Company Value Estimated By Tobin's Qmentioning
confidence: 99%